1997
DOI: 10.1111/j.1467-842x.1997.tb01791.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two strategies for dissemination of sun-protection policy in New South Wales primary and secondary schools

Abstract: With rising rates of skin cancer in Australia, there is a need to examine strategies to reduce sun exposure among children. This study aimed to determine the effectiveness of a multifaceted dissemination strategy compared with a simple mail-out strategy in promoting the adoption of comprehensive SunSmart skin protection policies and practices in primary and secondary schools in New South Wales. It also aimed to examine characteristics of the primary and secondary schools that adopted a comprehensive SunSmart p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The effect size reported in the trial (approximately 15 % relative to comparison schools) was consistent with those reported in controlled trials of interventions designed to assist large numbers of schools implement health promotion programs generally (13 %-45 %) [31,34,35,49,50]. On a population wide basis, a 15 % increase in the number of schools implementing vegetable and fruit programs is likely to represent a meaningful contribution to improving public health nutrition.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The effect size reported in the trial (approximately 15 % relative to comparison schools) was consistent with those reported in controlled trials of interventions designed to assist large numbers of schools implement health promotion programs generally (13 %-45 %) [31,34,35,49,50]. On a population wide basis, a 15 % increase in the number of schools implementing vegetable and fruit programs is likely to represent a meaningful contribution to improving public health nutrition.…”
Section: Discussionsupporting
confidence: 70%
“…In the above mentioned review of implementation interventions in community settings [26], those that have adopted a multi-strategy approach have reported a change in prevalence of program implementation of between 50 %-78 %. However, only a few of these studies have targeted a large number (>100) of schools [33-36] or utilized evaluation designs incorporating comparison groups [34,35,37], limiting the ability to infer causality.…”
Section: Introductionmentioning
confidence: 99%
“…Offer of information, program resources and instructional materials [45,46]: Program resources and instructional materials were delivered in the form of a resource package. This included, a guide manual with background and instructional information covering topics related to key physical activity promoting practices, three age appropriate structured activities handbooks, two DVDs demonstrating fundamental movement skills, laminated game cards and staff lanyards with pictorial and descriptive explanations of fundamental movement skills, a planning poster which identified timeframes for services to implement practice changes and, a fundamental movement skills template to assist with programming fundamental movement skills sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing a single mass mailing of evidence-based guidelines or a mass mailing plus a client-targeted letter with a control, no difference was found on practitioner behavior in a mental health context. Relatedly, a random assignment of schools implementing a skin care health program to either a mailed materials condition or a mailed materials + staff development module condition showed no differences in the sun protection instructional practices in either group (Schofield, Edwards, & Pearce, 1997). Educational research generally converges on the finding that training alone through single or multiple-series professional development (PD) workshops disseminating best-practice information does not result in positive implementation outcomes (Darling-Hammond, Wei, Andree, Richardson, & Orphanos, 2009;Garet, Porter, Desimone, Birman, & Yoon, 2001;Webster-Wright, 2009).…”
Section: Research Frameworkmentioning
confidence: 99%